Decision-Making Analysis for Optimal Durian Sales Location and Forward Integration Strategy for Sambeng Farm - Prastami, Hedyana Bunga (Syntax Literate, 2025)
This research addresses the optimal sales location and forward integration strategy for Sambeng Farm, a new venture in Indonesia's durian market. With the increasing domestic demand for durian, the study aims to identify a sales location that maximizes profitability while reducing reliance on intermediaries. Using the SMART (Simple Multi-Attribute Rating Technique) method, the research evaluates various criteria, including market potential, accessibility, and operational costs. A mixed-methods approach combined qualitative interviews with quantitative evaluations of potential locations. The findings indicate that Jakarta is the most advantageous site due to its large market size and high brand exposure, despite higher competition and cost. The study also reveals that forward integration—selling directly to consumers—significantly enhances profit margins compared to traditional sales through intermediaries. This strategic move allows Sambeng Farm to establish a premium brand image and increases overall profitability. The implementation plan outlined in the research emphasizes the importance of careful planning and execution over four years to ensure successful market entry. The implications of this study extend to other agricultural enterprises seeking to optimize sales strategies and enhance supply chain efficiency in similar markets. By providing insights into effective decision-making processes and strategic planning, this research contributes to the broader understanding of the durian industry in Indonesia.